Tingkat Pengetahuan Masyarakat Dan Pengunjung Tentang Obat Swamedikasi Dan Rasionalitas Di Dua Apotek Kecamatan Bandar Kabupaten Simalungun - Meyana Marbun; Shofian Syarifuddin; Wilson Samosir; Marolop Parlindungan Napitu; Muliati Muliati (Jurnal Kesehatan, 2020)
Self-medication, as the most widely used effort to treat minor illnesses, is still constrained by limited public knowledge about drugs and their use. This study was conducted to analyze the effect of education using leaflet media on the level of knowledge and rationality of self-medication use. This pre-experimental study used a one group pre-test/post-test study design. Respondents were visitors aged 18-59 years at two pharmacies in the Bandar sub-district, who had used oral medication to treat fever, cough, flu, pain, diarrhea and gastritis in the three months before the time of the study. Respondents were taken by consecutive sampling. Data collection was carried out through guided free interviews using a questionnaire that had been tested for validity and reliability. Leaflets containing information about self-medication were given to respondents after the pre-test was carried out. The number of respondents obtained was as many as 97 respondents. All of these respondents were contacted again by telephone after 4-5 weeks of education, to do a post-test using the same questionnaire used during the pre-test. The Wilcoxon test and McNemar test were used to statistically analyze the data obtained. Based on the results of this study, it can be concluded that education can significantly increase self-medication knowledge (p = 0.000) and the rationality of respondents' self-medication use (p = 0.015).